Traditional medicine practices of Guji Semi-Pastoralist People to treat livestock ailments in Suro Barguda District, West Guji Zone, Ethiopia - Eshete, Mersha Ashagre; Lulekal Molla, Ermias (Ethnobiology and Conservation, 2022)
The objectives of this research were to collect, identify, document, and analyze ethnoveterinary medicinal plants and their associated indigenous knowledge including their preparation and application by traditional healers, and the status of their conservation by Guji Semi-Pastoralist People of Suro Barguda District, West Guji Zone, Oromia Regional State, Ethiopia.  Forty-six ethnoveterinary medicinal plant species representing 43 genera and 29 families were identified in the district (Additional file 1). About 26.1% of the families were represented by more than one species. The highest number of species was recorded for Asteraceae (5 species), followed by Euphorbiaceae (4 species) and most ethnoveterinary medicines were prepared from herbs and shrubs than other growth forms. Chopping the remedial parts and homogenizing them with cold water was found to be the major mode of remedy preparation. All documented ethnoveterinary plant species were harvested from the wild and observed as exposed to depletion. About 4.4% of the ethnoveterinary medicinal plants of Suro Barguda District were endemic to Ethiopia. This study indicated that the study area encompasses different species of ethnoveterinary medicinal plants which should be given conservation priority and the local community depends largely on these plants for the treatment of different livestock ailments although the healers had a very high intention to keep their traditional knowledge secrete. The indigenous knowledge of pastoralists about plants and breeding different species of livestock, as well as their environmental management systems (traditional forest, soil, and water conservation systems), should be incorporated in the planning and implementation of developmental interventions.